OPTIMALISASI PENERAPAN TEKNOLOGI VIRTUAL REALITY TOUR KAMPUS UNIVERSITAS MAJALENGKA MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE: Indonesia - Tri Ferga Prasetyo; Ade Bastian; Harun Sujadi (Universitas Majalengka, 2021)
Campus introduction media in general still use billboards and brochures or advertisements, therefore the use of Virtual Reality technology is very good to use. Optimizing the application of this technology is made to build an interactive application that can visualize the facilities and infrastructure at University Majalengka in the form of 360 images and videos to make it easier for users to digitally view the facilities and infrastructure of the University Majalengka Campus. The method used in this research is MDLC (Multimedia Development Life Cycle). This method can optimize the manufacturing process and application of technology used in a smartphone media that is integrated with other media or 3D media. MDLC rule pattern itself by prioritizing interactive rests on the user. This application was built using the C # programming language with Unity 3D software. The final result of this research is the creation of a virtual tour application of the University Majalengka Campus which can be used by users to view interactive digital facilities and infrastructure on campus with a 360 degree angle using a smartphone that has a Gyroscope sensor which can be integrated with the paired virtual reality technology. into virtual reality glasses.